2015
DOI: 10.1016/j.bbi.2014.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Tumor growth increases neuroinflammation, fatigue and depressive-like behavior prior to alterations in muscle function

Abstract: Cancer patients frequently suffer from fatigue, a complex syndrome associated with loss of muscle mass, weakness, and depressed mood. Cancer-related fatigue (CRF) can be present at the time of diagnosis, during treatment, and persists for years after treatment. CRF negatively influences quality of life, limits functional independence, and is associated with decreased survival in patients with incurable disease. Currently there are no effective treatments to reduce CRF. The aim of this study was to use a mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
112
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 50 publications
12
112
2
1
Order By: Relevance
“…Increased neuroinflammation, for example increased brain IL-1β expression, has been linked to both depressed mood [15] and fatigue [16]. Using a mouse model of CRF, we have previously shown that increased expression of pro-inflammatory cytokines within the CNS is associated with behavioral measures of fatigue, such as decreased voluntary wheel running (VWRA) activity, measures of weakness, such as reduced grip strength, and depressed mood, such as immobility during the forced swim test (FST) and anhedonia [17]. Treatment with minocycline, a drug that reduces brain synthesis of inflammatory cytokines, reduced depressive-like behaviors and improved grip strength in tumor-bearing mice [17].…”
Section: Introductionmentioning
confidence: 99%
“…Increased neuroinflammation, for example increased brain IL-1β expression, has been linked to both depressed mood [15] and fatigue [16]. Using a mouse model of CRF, we have previously shown that increased expression of pro-inflammatory cytokines within the CNS is associated with behavioral measures of fatigue, such as decreased voluntary wheel running (VWRA) activity, measures of weakness, such as reduced grip strength, and depressed mood, such as immobility during the forced swim test (FST) and anhedonia [17]. Treatment with minocycline, a drug that reduces brain synthesis of inflammatory cytokines, reduced depressive-like behaviors and improved grip strength in tumor-bearing mice [17].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, animal rat models of cancer-induced fatigue suggested that behavioral alterations occur in parallel with the increased expression of IL-1β mRNA in the cortex and the hippocampus 176 .…”
Section: Physical Activitymentioning
confidence: 99%
“…Fatigue significantly limits quality of life, reduces psychosocial functioning and is an independent predictor of decreased survival in individuals with terminal disease 175 . Recent advances in the neurobiology of fatigue revealed that it is more likely to be related to biological pathways promoting neuroinflammation than with primary alterations involving the muscles 176 .…”
Section: Physical Activitymentioning
confidence: 99%
“…Other peripheral tumors increase resting neuroinflammatory signals [39,40] and a rat model of breast cancer is characterized by exaggerated neuroinflammatory responses to a peripheral LPS injection relative to tumor-free controls [22]. Larger tumor masses may be necessary for these increases in resting and triggered neuroinflammatory signals, as a positive association between tumor mass and neuroinflammation has been observed [22].…”
Section: Discussionmentioning
confidence: 99%